Validation of Experimental Study and SimulationOTEC Power Plant using Shell-Tube Heat Exchanger Materials with Copper, Tin, and Working Fluid Ammonia - Mawardi, Mawardi; Siregar, Zufri Hasrudy; Nugraha, Yoga Tri; Rida, Rizkha; Fahri , Tengku Muhammad; Irwanto, Muhammad (Jurnal Rekayasa Mesin, 2026)
The results of experimental research on marine thermal power plants using a shell and tube heat exchanger made of copper-tin (Cu-Sn) alloy are the main focus of this study. This study uses a heat exchanger Scale Model measuring 60 mm wide x 1 meter long. The system operated using a closed cycle and Organic Rankin cycle. A simulation study has been carried out using Ansys CFD software to model new heat exchangers, namely models A and B. The interaction between ammonia and hot water produces thermodynamic values in the form of an evaporator outlet temperature of 28°C in models A and B 260C. The weakness of model B is that the turbulent flow is divided into left and right sides so that heat loss occurs in the flow corner area. The seawater inlet temperature of 29°C can heat the working fluid from the ammonia flow inlet from 5°C to 28°C, resulting in saturated steam reaching 5-6 bar.